The Multiplier Effect of Tourism on the Local Economy (Case Study of Aryakibans Land Tourism, Rajagaluh Kidul Village, Majalengka) - Reza Rahmat; Arni Muslimah Handayani Widjaja (Riviera Publishing, 2026)
The tourism industry is a development priority that contributes to regional economic growth and job creation. However, a significant research gap remains regarding economic circulation within community-based and independently managed tourism sites, as most existing literature focuses on highly structured or established destinations. This study aimed to examine the multiplier effect of tourism activities at Aryakibans Land on the local economy of Rajagaluh Kidul Village, Rajagaluh District, Majalengka Regency, with particular emphasis on direct, indirect, and induced economic impacts. This study employed a descriptive quantitative approach. Primary data were collected through structured questionnaires from tourists, local business owners, and employees using proportional stratified random sampling. The data were analyzed by calculating the Keynesian Income Multiplier and Ratio Income Multiplier Type I and Type II to assess economic circulation generated by tourism activities. The findings provided a quantitative depiction of the economic circulation resulting from visitor expenditures on household income and local business activities. The results indicated that the self-managed tourism model at Aryakibans Land demonstrated potential to generate sustainable economic multiplier effects within the local community. These findings suggest that optimizing community-based tourism infrastructure can serve as a practical strategy to enhance grassroots economic development and provide strategic input for local government policymaking.